Pinhão-bravo (jatropha mollissima pohl baill.): caracterização fitoquímica e atividades farmacológicas do látex e dos seus extratos - Queiroz Neto, Rafael Fernandes de (2018)
Jatropha (Jatropha mollissima Pohl Baill) is an autochthonous shrub native to caatinga vegetation, found in much of the semi-arid region of the Brazilian Northeast, used in popular culture for therapeutic purposes. The latex of Jatropha and extracts derived from it were evaluated for phytochemical composition, identifying the main secondary metabolites from qualitative and quantitative methods, and their pharmacological activities. Toxicity was investigated, through the acute toxic dose in Wistar rats, antioxidant action, according to the photocolorimetric method of free radical DPPH, and antibacterial action, through minimum inhibitory concentration and minimum bactericidal concentration. Phenols, tannins, flavonoids and saponins were detected in latex and other extracts. Both latex and ethanolic extract presented moderate antioxidant activity, as well as anti-bacterial activity against Gram-positive (Staphylococcus aureus, Streptococcus agalactiae, Streptococcus pyogenes, Streptococcus mutans and Enterococcus faecalis) and Gram-negative strains (Shigella flexneri, Escherichia coli, Klebsiella pneumoniae, Salmonella typhimurium and Pseudomonas aeruginosa) in various dilutions along with the hydroalcoholic extract. Jatropha´s latex also showed low acute toxicity in rats. Therefore, the results obtained in this research corroborate the popular use of J. mollissima and its therapeutic potential